Volume 7: Turbomachinery, Parts a and B 2009
DOI: 10.1115/gt2009-59185
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Gas Turbine Rotating Cavities by an One-Dimensional Model

Abstract: Reliable design of secondary air system is one of the main tasks for the safety, unfailing and performance of gas turbine engines. To meet the increasing demands of gas turbines design, improved tools in prediction of the secondary air system behavior over a wide range of operating conditions are needed. A real gas turbine secondary air system includes several components, therefore its analysis is not carried out through a complete CFD approach. Usually, that predictions are performed using codes, based on sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Lately, Baldassarre, et al [30] have developed 1D software to estimate radial pressure distribution along impeller surfaces, and subsequently, the total axial thrust acting on the rotor; they validate the model using the experimental data from two highpressure centrifugal compressors tested at full load. In that work they used the correlation of Da Soghe, et al [31].…”
Section: Axial Forcementioning
confidence: 99%
“…Lately, Baldassarre, et al [30] have developed 1D software to estimate radial pressure distribution along impeller surfaces, and subsequently, the total axial thrust acting on the rotor; they validate the model using the experimental data from two highpressure centrifugal compressors tested at full load. In that work they used the correlation of Da Soghe, et al [31].…”
Section: Axial Forcementioning
confidence: 99%
“…It is recommended that some investigation of the flow field is attempted by means of CFD or rig testing. In particular, Da Soghe et al [23] showed the usefulness of CFD to characterize the vortex in a rotating cavity for a range of operating conditions. On the other hand, the time scales of the problem under scrutiny would require expensive and complicated experimental testing.…”
Section: Current Model Capabilitymentioning
confidence: 99%
“…A well designed one-dimensional model could monitor the detailed behavior of the gas turbines components in real-time. Such models are very effective in real-world control systems and are being used in power and electricity generation plants [1][2][3][4]. Air compressor as one of the main components of gas turbines has to be modeled in one-dimensional form, while gas turbine is being modeled as one-dimensional [5].…”
Section: Introductionmentioning
confidence: 99%